Diagnostic odyssey in severe neurodevelopmental disorders: toward clinical whole‐exome sequencing as a first‐line diagnostic test. Issue 6 (26th April 2016) - Thevenon, J.; Duffourd, Y.; Masurel‐Paulet, A.; Lefebvre, M.; Feillet, F.; El Chehadeh‐Djebbar, S.; St‐Onge, J.; Steinmetz, A.; Huet, F.; Chouchane, M.; Darmency‐Stamboul, V.; Callier, P.; et al.
Abstract : The current standard of care for diagnosis of severe intellectual disability (ID) and epileptic encephalopathy (EE) results in a diagnostic yield of ∼50%. Affected individuals nonetheless undergo multiple clinical evaluations and low‐yield laboratory tests often referred to as a 'diagnostic odyssey'. This study was aimed at assessing the utility of clinical whole‐exome sequencing (WES) in individuals with undiagnosed and severe forms of ID and EE, and the feasibility of its implementation in routine practice by a small regional genetic center. We performed WES in a cohort of 43 unrelated individuals with undiagnosed ID and/or EE. All individuals had undergone multiple clinical evaluations and diagnostic tests over the years, with no definitive diagnosis. Sequencing data analysis and interpretation were carried out at the local molecular genetics laboratory. The diagnostic rate of WES reached 32.5% (14 out of 43 individuals). Genetic diagnosis had a direct impact on clinical management in four families, including a prenatal diagnostic test in one family. Our data emphasize the clinical utility and feasibility of WES in individuals with undiagnosed forms of ID and EE and highlight the necessity of close collaborations between ordering physicians, molecular geneticists, bioinformaticians and researchers for accurate data interpretation. Abstract :